2011
DOI: 10.1007/s11105-011-0330-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Molecular Characterization of a SERK Gene Transcriptionally Induced During Somatic Embryogenesis in Ananas comosus cv. Shenwan

Abstract: A somatic embryogenesis receptor-like kinase (SERK) gene, designated as AcSERK1, was isolated from pineapple (Ananas comosus cv. Shenwan). AcSERK1 shared all the characteristic domains of the SERK family, including five leucine-rich repeats, one proline-rich region motif, transmembrane domain, and kinase domains. Somatic embryogenic cultures of pineapple were established following transfer of callus cultures to Murashige and Skoog (1962) medium containing 2,4-dichlorophenoxyacetic acid. The role of AcSERK1 dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 28 publications
(35 reference statements)
7
44
0
2
Order By: Relevance
“…This gene can be used as a marker of embryogenic competent cells (Ma et al, 2012). In present study, another SERK gene, AcSERK2, was identified in pineapple.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…This gene can be used as a marker of embryogenic competent cells (Ma et al, 2012). In present study, another SERK gene, AcSERK2, was identified in pineapple.…”
Section: Introductionmentioning
confidence: 63%
“…1a). This exon/intron structure is quite similar to AcSERK1 (Ma et al, 2012) and other SERKs (Sharma et al, 2008;Stone et al, 2001). Each LRR domain is encoded by a separate exon, except for LRR2 and LRR3, which shared a single exon.…”
Section: Sequence Analysismentioning
confidence: 68%
See 2 more Smart Citations
“…The involvement of SERK proteins in regulating somatic embryogenesis was first described for DcSERK in embryogenic cell suspension cultures of carrot more than 15 years ago (Schmidt et al, 1997). Since then SERK gene homologs have been identified and their role in mediating somatic embryogenesis demonstrated in several monocot and dicot species such as Arabidopsis thaliana , Medicago truncatula (Nolan et al, 2003), Triticum aestivum (Singla et al, 2008), Vitis vinifera (Maillot et al, 2009), Cocos nucifera (Pérez-Núñez et al, 2009), Ananas comosus (Ma et al, 2012) and Cyrtochilum loxense (Cueva et al, 2012). Moreover, a gymnosperm SERK homolog has recently been discovered and its association with somatic embryogenesis was shown (Steiner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%